Penerapan Etika Pustakawan Dalam Pembentukan Karakter Budaya Kerja Pustakawan Di Dinas Perpustakaan Dan Arsip Provinsi Sumatera Utara - Rafika Zahara Ginting; Khoirul Jamil; Yusniah Yusniah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This study aims to determine whether librarians are friendly and gentle in carrying out their duties as librarians in the character of work culture at the Library and Archives Service of North Sumatra Province. This type of research is descriptive with a qualitative approach. In this research data collection techniques using interview techniques, observation and documentation. While the data analysis technique goes through four stages including data collection, data reduction, data presentation and drawing conclusions. The location of this research was conducted at the Library and Archives Service of North Sumatra Province. The results of this study indicate that in the application of librarian ethics in the formation of the character of work culture, they have applied their ethics well as librarians according to the rules in the library. Such as librarian ethics in social interaction, librarian ethics with colleagues, librarian ethics in serving users and librarian ethics with superiors. And as for the obstacles to librarians in applying librarian ethics such as lack of communication, unresponsive service and the attitude of librarians.